Curriculum Evaluation: Inputs for Principal’s Instructional Leadership - Gilbert S. Arrieta (International Journal of Social Learning (IJSL), 2021)
One of the most important components in education is the curriculum. It undergoes evaluation and development to be responsive to the needs of the times. It adapts to the kind of teachers and learners because teaching and learning are dynamic. The main drivers of the curriculum are the education leaders primarily the principals who are the instructional leaders. The main task of the principal is instructional leadership which means overseeing the teaching and learning process starting with the curriculum. However, the administrative tasks of the principals deprive them of becoming effective instructional leaders. This study aims to present the experiences of the researcher in curriculum evaluation under different principals in a private sectarian school in Manila and seeks to identify how principals can take a strong leadership presence in the challenges in instruction and curriculum evaluation. A critical reflection which is an extension of “critical thinking” and asks us to think about our practice and ideas and then it challenges us to step back and examine our thinking by asking probing questions was used as the method in this study. The researcher looks back into his experiences and identifies the key points in curriculum evaluation vis-à-vis the tasks of instructional leadership. It found out that curriculum evaluation, primarily an integral part of instructional leadership. The principals have to do curriculum evaluation as a collaborative task and process. Moreover, curriculum evaluation with instructional leadership should be giving importance to professional development and mentoring of academic heads and teachers.